A Study On The Design And Use Of Performance Management System In China’s Innovative Start-ups - Hung, Wai Chung Clarence (2023)
China’s start-ups market has grown rapidly since the Chinese Government encouraged new ventures and announced the “mass entrepreneurship and innovation” initiative in 2015. Nevertheless, start-ups’ failure rate can be as high as 95%, partly due to the lack of Performance Management Systems (PMSs) in managing and controlling organisations. PMSs are designed based on Western, well-established organisations. Existing research relating to PMSs in China, concerning their design and use in innovative start-ups, is scarce. Therefore, this study aimed to examine the types of PMSs adopted in China’s innovative start-ups, and how the systems are designed and used under the influence of Chinese culture and start-up managers’ personality traits. This study adopted a qualitative case study approach for four selected start-up companies, with data collected through the use of semi-structured interviews, field observations and document reviews to examine their management control behaviours. One of the four case companies was purposely selected as a contrasting case for identifying the similarities and differences among case ownermanagers in order to uncover the underlying influence of their behaviours. The GLOBE theory, the Traits Theory of Personality, and the Theory of Circumscription and Compromise were used to underpin the findings and discussions. The findings revealed that the Chinese owner-managers used simplified and informal PMSs, through personnel and social controls, in their organisations